SEAGRASS BEDS DISTRIBUTION AND THEIR STRUCTURE IN THE SURROUNDING COASTAL WATERS OF KAPOPOSANG ISLAND, SOUTH SULAWESI - Nadiarti Nadiarti; Etty Riani; Ita Djuwita; Sugeng Budiharsono; Ari Purbayanto (Graduate School Bogor Agricultural University (SPs IPB), 2012)
Kapoposang Island and the surrounding waters has been appointed by Indonesian Governmet to be a part of waters tour park in South Sulawesi, implying the requirement of the marine resources, including seagrass ecosystems in this area, should be well managed in order to provide biodiversity protection and sustainable use of the seagrass ecosystems. For this purpose, one of basic required information is seagrass distribution and habitat structure. This study was aimed to 1) observe the location of continues seagrass beds, 2) identify the habitat structure in each site of continues seagrass beds. A combination of visual observation and transect method was applied to determine the sites of continues seagrass beds, while seagrass habitat structure was identified based on ecological habitat structure model. Study results revealed that continues seagrass beds were only found in five different sites of Kapoposang coastal waters. Seagrass habitat structure among the five sites were in variable and the highest seagrass cover was found in two sites, namely 1) site A in the north-west part of the island (S04o41'42.5